Preparation of PAN Spinning Solution with Fine Dispersion of Cellulose Microparticles - Jee-Woo Yang; Jong Sung Won; Da Young Jin; Ji Eun Lee; Won Ho Park; Seung Goo Lee (Advances in Materials Science and Engineering)
This study suggested the optimum conditions for the stable dispersion of cellulose microparticles in PAN spinning dope, which was prepared for spinning the fiber. Many research studies have investigated methods for preparing a variety of carbon fiber precursors in an attempt to control their characteristics according to the applications. In order to prepare PAN fiber that contains fine cellulose particles, it is important to create a uniformly dispersed spinning dope. Minimization of the cellulose particle size was subjected to heat treatment at various temperatures in order to reduce the cohesive force from the hydrogen bonds between the cellulose molecules. Carbonized cellulose microparticles were obtained for efficient dispersion using the physical method and the sedimentation method. Several instrumental analyses were conducted to study the characteristics of the particles and solutions with SEM, FT-IR, XRD, and a particle size analyzer. From the results, the dispersion of the PAN spinning dope with a chemical treatment was superior to the milling method followed by heat treatment. In this study, heat-treating cellulose microparticles at 400°C was found to be the most effective method.